Contribution to the analytical calculation of the performances of a motor vehicle equipped with a hydrodynamic torque converter - Demić, Miroslav D.; Glišović, Jasna D. (Vojnotehnički glasnik / Military Technical Courier, 2018)
Hydrodynamic torque converters (hereinafter referred to as HDTC) are becoming increasingly widespread in motor vehicles. The internal combustion engine (ICE) and the HDTC system can be viewed as one aggregate the output characteristics of which are uniquely defined by the characteristics of the engine and the corresponding HDTC. Namely, the engine and the hydro-converter can be considered as one system, with a precisely defined output torque and output angular velocity. This creates a possibility that the drive force can be calculated as if it is a mechanical transmission, in which the output torque of the hydro-converter is the input into the planetary gears train (if any). Harmonizing the joint work of the ICE-HDTC is a complex process. An attempt has been made in this paper to make a model of the aforementioned system in order to harmonize more easily the characteristics of the combined operation of the internal combustion engine and the HDTC.